(untitled) (European Journal of Formal Sciences and Engineering, 2024)
In this proposed paper, a single band microstrip patch antenna for fifth generation (5G) wireless application was presented. 28, 38, 60 and 73 GHz frequency bands have been allocated for 5G mobile communications by International Telecommunications Union (ITU). In this paper, we proposed an antenna, which is suitable for the millimeter wave frequency. The single band antenna consists of new slot loaded on the radiating patch with the 50 ohms microstrip line feeding used. This single band antenna was simulated on a FR4 dielectric substrate have relative permittivity 4.4, loss tangent 0.02, and height 1.6 mm. The antenna was simulated by Electromagnetic simulation, computer software technology High Frequency Structural Simulator. And simulated result on return loss, VSWR, radiation pattern and 3D gain was presented. The parameters of the results well coherent and proved the literature for millimeter wave 5G wireless application at 38 GHz.